2011
DOI: 10.1016/j.it.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Orchestrating house dust mite-associated allergy in the lung

Abstract: House dust mites (HDM; Dermatophagoides sp.) are one of the commonest aeroallergens worldwide and up to 85% of asthmatics are typically HDM allergic. Allergenicity is associated both with the mites themselves and with ligands derived from mite-associated bacterial and fungal products. Murine models of allergic airways disease for asthma research have recently switched from the use of surrogate allergen ovalbumin together with adjuvant to use of the HDM extract. This has accelerated understanding of how adaptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
374
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 357 publications
(389 citation statements)
references
References 105 publications
(117 reference statements)
8
374
0
7
Order By: Relevance
“…These mice have no overt developmental or phenotypic defects and are born at normal Mendelian ratios. To induce type 2 immune responses, we decided to use HDM because, as one of the common allergens, HDM is a very pathologically relevant agent (1). First, we wanted to determine the levels of chitin in HDM (Greer Laboratories).…”
Section: Amcase-ed Mice Show Enhanced Type 2 Immune Responses Tomentioning
confidence: 99%
See 4 more Smart Citations
“…These mice have no overt developmental or phenotypic defects and are born at normal Mendelian ratios. To induce type 2 immune responses, we decided to use HDM because, as one of the common allergens, HDM is a very pathologically relevant agent (1). First, we wanted to determine the levels of chitin in HDM (Greer Laboratories).…”
Section: Amcase-ed Mice Show Enhanced Type 2 Immune Responses Tomentioning
confidence: 99%
“…It is well known that HDM instructs a type 2 immune response via the release of innate pro-Th2 cytokines including TSLP, IL-25, and IL-33 (1,3,26). Indeed, a recent report that showed that IL-33, but not TSLP or IL-25, is central to mite and peanut allergic sensitization led us to focus on IL-33 (27).…”
Section: Hdm Promotes Increased Il-33 Production In Amcase-ed and Casmentioning
confidence: 99%
See 3 more Smart Citations